Paratransit Trip Data Collection System with Smartphone GPS and REST Web Service in Malang, Indonesia - Agi Putra Kharisma; Eriq Muhammad Adams Jonemaro; Issa Arwani (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Paratransit in Malang has its own irregular characteristics, same as in other cities in the world. It is tough to recognize the exact operational time, availability, and estimated travel time when using paratransit. The information about paratransit can be only obtained by making predictions due to its irregular characteristics. This research examined the importance of a system that can collect paratransit travel data as a basis for making predictions. Therefore, this research proposes the design of a paratransit travel data collection system by utilizing smartphone GPS and REST web service. To determine the position of the paratransit, the researchers used the concept of circle-based geofencing which is called pseudo-stop. The initial results obtained from the experiment indicated the influence of tracking intervals and radius of pseudo-stop on effectiveness and efficiency of the system. The shorter the tracking interval, the higher the tendency of the pseudo-stop radius value to decrease, resulting in decreased effectiveness and increased efficiency. Otherwise, the wider the tracking interval, the higher the tendency of the pseudo-stop radius value to be greater, resulting in increased effectiveness and decreased efficiency. In spite of periodically accessing location providers, the energy usage is quite low.